Adipokines as biochemical marker of polycystic ovary syndrome in adolescents – review - Orszulak, Dominika; Niziński, Kacper; Matonóg, Aleksandra; Zięba-Domalik, Maja; Stojko, Rafał; Drosdzol-Cop, Agnieszka (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting approximately 10% of adolescent women. According to literature data, in the case of coexistence of obesity and PCOS, menstrual cycle disorders are much more common. One of the probable reasons is the activity of adipose tissue, which secretes many types of adipokines that may have a negative impact on hormonal and metabolic functions. This article reviews the literature on the role of adipokines in the etiopathogenesis of PCOS in adolescent girls. The literature base consisted of published articles - clinical trials, meta-analyses, reviews and systematic reviews. The databases - PubMed, ScienceDirect, EMBASE were searched.